1993
DOI: 10.1046/j.1365-2648.1993.18081202.x
|View full text |Cite
|
Sign up to set email alerts
|

School nursing: history, present practice and possibilities reviewed

Abstract: A review of the literature revealed that the early school nurses were engaged in predominantly screening work and as assistants to the school medical officer. The relatively limited empirical work suggests that they have the potential to make a major contribution to the health of school children; however, their current role appears to vary enormously nationwide and the issues of competency for the role and integration into the school team need addressing. The consumer/outsider view literature indicated a misma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Working consistently within the same 'physical' space (caseload) also provides a sense of ownership and familiar understanding (Kelly et al, 2005) and it takes time to build relationships with schools, young people and their families (Sherwin, 2016). The visibility of the service has historically been a key issue, which is largely due to the relatively small workforce (While and Barriball, 1993;BYC, 2011). To provide support on a practical level school nurses need to be physically visible so young people know who to contact and how to access them.…”
Section: Accessibilitymentioning
confidence: 99%
“…Working consistently within the same 'physical' space (caseload) also provides a sense of ownership and familiar understanding (Kelly et al, 2005) and it takes time to build relationships with schools, young people and their families (Sherwin, 2016). The visibility of the service has historically been a key issue, which is largely due to the relatively small workforce (While and Barriball, 1993;BYC, 2011). To provide support on a practical level school nurses need to be physically visible so young people know who to contact and how to access them.…”
Section: Accessibilitymentioning
confidence: 99%
“…There is a paucity of research literature on the subject of how nursing time is spent in schools, and on how school nurses and their educational colleagues view the role of the school nurse. Studies on the perception of school nurse roles show significant disagreement among nurses and teachers, nurses and school counselors, and nurses and principals, in the functions of a school nurse, particularly in regard to first aid administration (Barriball, 1993; Greenhill, 1977; and Maughan & Adams, 2011). Teachers, more so than nurses, viewed school nursing services as consistent with cultural expectations of nurses in general: That nurses primarily perform discrete clinical–as opposed to public health and educational–tasks to care for sick and injured students.…”
Section: Perception Reality and Unintended Outcomesmentioning
confidence: 99%
“…In 1995, the WHO launched the Global School Health Initiative to strengthen school health programmes at local, regional, national and global levels (Wicklander 2005 Although expectations of school nursing have increased, the extent of the workforce and scope of practice remain unclear (Lightfoot & Bines 2000, Ball & Pike 2005. The 'invisibility' of research into school nursing (While & Barribel 1993) and its absence (Lightfoot & Bines 2000) have also been noted. In 2000, Clark et al reported that in Wales the school nursing service was under-developed and under-resourced, the number of school nurses having fallen during the 1990s.…”
Section: Introductionmentioning
confidence: 99%